Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Why is it true that $$\frac{\varphi(m)}{m}\sum_{n \leq x}\frac{1}{n} \leq \sum_{n \leq x, (n, m) = 1}\frac{1}{n}?$$ Intuitively to see this, one can think of that from 1 up to $m$, there are $\varphi(m)$ integers which are relative prime to $m$, so one can expect this to be the proportion, but how does one show this explicitly?

share|cite|improve this question
Why do you believe this is true? Where does it come from? – David Speyer Nov 26 '12 at 20:31
Put it this way: can you prove it if $m$ is a prime or a prime power? Plus, where did you find it? – Will Jagy Nov 27 '12 at 0:13

We proceed by induction on $k$, the number of distinct prime factors of $m$.

When $k=0$, we have $m=1$, and $$\frac{\varphi(1)}{1}\sum_{n \leq x}\frac{1}{n}=\sum_{n \leq x}\frac{1}{n}=\sum_{n \leq x, (n, 1) = 1}\frac{1}{n}$$

Suppose that the statement holds for $k=i \geq 0$. Consider $m$ with $i+1$ distinct prime factors, and let $m=p^ab, a \geq 1$, where $b$ has $i$ distinct prime factors, and $p \nmid b$.

Then by the induction hypothesis,

$$\frac{\varphi(p^ab)}{p^ab}\sum_{n \leq x}\frac{1}{n}=\frac{\varphi(p^a)}{p^a}\frac{\varphi(b)}{b}\sum_{n \leq x}\frac{1}{n} \leq \frac{p-1}{p}\sum_{n \leq x, (n, b) = 1}\frac{1}{n}$$

We have

\begin{align} \sum_{n \leq x, (n, p^ab) = 1}\frac{1}{n}=\sum_{n \leq x, (n, b) = 1}\frac{1}{n}-\sum_{n \leq x, (n, b) = 1, p \mid n}\frac{1}{n} &=\sum_{n \leq x, (n, b) = 1}\frac{1}{n}-\frac{1}{p}\sum_{n \leq \lfloor \frac{x}{p} \rfloor, (n, b) = 1}\frac{1}{n} \\ & \geq \sum_{n \leq x, (n, b) = 1}\frac{1}{n}-\frac{1}{p}\sum_{n \leq x, (n, b) = 1}\frac{1}{n} \\ & =\frac{p-1}{p}\sum_{n \leq x, (n, b) = 1}\frac{1}{n} \\ & \geq \frac{\varphi(p^ab)}{p^ab}\sum_{n \leq x}\frac{1}{n} \end{align}

We are thus done by induction.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.